Boosting immune response against cervical cancer: A combined approach using oncolytic virus and targeted therapies - Hedieh Zargaran; Amir Ghaemi; Mohammad Shenagari; Mehdi Samadi (PLoS ONE, 2025)
Background Cervical cancer remains a primary reason for cancer malignancy among women worldwide, primarily due to human papillomavirus (HPV) strains HPV16 and HPV18. Despite having access to vaccines, there are few treatment options for advanced or recurring cases. This research investigates the possibility of using Newcastle disease virus (NDV) along with Everolimus (EVE) and Beclin-1 (BEC) to improve immune reactions and decrease tumor development in an experimental model of HPV-related cervical cancer. Methods A mouse model for cervical cancer was created by utilizing HPV16 E6/E7-expressing TC-1 cells in C57BL/6 mice. The mice underwent treatment with NDV, EVE, BEC, or various combinations of these therapies. Tumor progression was monitored, evaluated immune responses by measuring cytokine levels (including IL-4, IFN-γ, and IL-12), and investigated the presence of CD8 + T cells within the tumors. Additionally, survival rates were monitored throughout the study. Results The synergy of NDV, EVE, and BEC led to a remarkable decrease in tumor growth, achieving reductions of as much as 70% when compared to monotherapies. Additionally, our combination therapy elicited strong immune reactions, evidenced by increased concentrations of IL-4, IFN-γ, and IL-12, along with enhanced infiltration of CD8 + T cells into the tumors. Mice that were subjected to this Triple therapy exhibited better survival rates than those in other treatment categories. Conclusions Our findings highlight the potential to improve outcomes in cervical cancer associated with HPV through a multi-faceted approach incorporating NDV, Everolimus, and Beclin-1. This therapeutic strategy not only hinders tumor growth but also strengthens the immune system’s ability to fight against cancer. These results prompt further exploration of this combination in clinical trials, with the goal of offering new treatment avenues for patients who have limited choices.